Computing the Constant Elasticity of Variance Option Pricing Formula - SCHRODER, MARK (Journal of Finance, 1989)
ABSTRACT This paper expresses the constant elasticity of variance option pricing formula in terms of the noncentral chi‐square distribution. This allows the application of well‐known approximation formulas and the derivation of a whole class of closed‐form solutions. In addition, a simple and efficient algorithm for computing this distribution is presented.